Speaking self-assessment: Mismatches between learners' and teachers' criteria. (July 2016) - Babaii, Esmat; Taghaddomi, Shahin; Pashmforoosh, Roya
Perceptual (mis)matches between teachers and learners are said to affect learning success or failure. Self-assessment, as a formative assessment tool, may, inter alia, be considered a means to minimize such mismatches. Therefore, the present study investigated the extent to which learners' assessment of their own speaking performance, before and after their being provided with a list of agreed-upon scoring criteria followed by a practice session, matches that of their teachers. In so doing, 29 EFL learners and six EFL teachers served as participants; the learners were asked to assess their audio-recorded speaking performance before and after their being provided with the scoring criteria and practice session. The teachers were also asked to assess the learners' performance according to the same criteria. Finally, the learners were required to evaluate the effectiveness of doing self-assessment in the form of reflection papers. The results revealed a significant difference between the learners' assessment of their own speaking ability on the two occasions. The findings also suggested that providing the learners with the scoring criteria and the follow-up practice session minimized the existing mismatches between learner assessment and teacher assessment. Moreover, the inductive analysis of the reflection papers yielded a number of themes suggesting that, despite some limitations, the learners' overall evaluation of the effectiveness of speaking self-assessment was positive.